Analisis Pelanggaran Etika Profesi Akuntansi : (Studi Kasus pada PT. Indofarma, Tbk) - Saridawati Saridawati; Lina Agustin; Raihani Aprilia; Riska Amanda; Selfa Gaduh Kharisma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze violations of accounting professional ethics at PT Indofarma Tbk, a state-owned pharmaceutical company in Indonesia. The case gained public attention following an investigative audit report by the Audit Board of the Republic of Indonesia (BPK), which revealed financial statement manipulation causing state losses amounting to IDR 371.83 billion. This research employs a qualitative approach using a case study method. Data were obtained through the analysis of financial statements, BPK audit findings, as well as relevant literature and publications. The findings indicate violations of several fundamental ethical principles, including integrity, objectivity, professional competence, confidentiality, and professional behavior. The main contributing factors, based on the fraud triangle theory, are financial pressure, opportunity arising from weak internal controls, and rationalization by management. This case emphasizes the importance of implementing professional accounting ethics and strong oversight in the preparation of financial statements to maintain public trust and corporate integrity. The study implies the urgent need to strengthen internal control systems and enforce ethical standards as preventive measures against fraud.